Estimating demand schedules in hedonic analysis: The case of urban parks - Toke Emil Panduro; Cathrine Ulla Jensen; Thomas Hedemark Lundhede; Kathrine von Graevenitz; Bo Jellesmark Thorsen (University of Copenhagen, Department of Food and Resource Economics (IFRO), 2016)
The hedonic pricing method has been used extensively to obtain implicit prices for availability of urban green space, but few hedonic studies have obtained households' preference parameters. We estimate willingness to pay functions for park availability in Copenhagen using an approach that places identifying restrictions on the utility function. We do this for two different measures of park availability. We apply our results to a policy scenario and show how estimates of aggregate welfare changes are highly sensitive to the measure of park availability applied. Thus, the approach in this study applies an alternative path for estimation of demand schedules for public goods using hedonic data. The findings also stress the importance of paying attention to how public goods are defined when undertaking welfare economic policy analyses.
Keywords: R21; Q51; 330; hedonic house price model; green space; preference heterogeneity; identification